The changing characteristics of patients with chronic hepatitis C prescribed direct acting antiviral medicines in general practice since listing of the medicines on the Australian Pharmaceutical Benefits Scheme. Issue 7 (18th June 2021) - Busingye, Doreen; Chidwick, Kendal; Simpson, Vanessa; Dartnell, Jonathan; J Dore, Gregory; Balcomb, Anne; Blogg, Suzanne
Abstract: Background and Aim: The primary objective of this study was to determine whether the characteristics of patients prescribed direct acting antiviral (DAA) medicines have changed since initial listing of the medicines on the Australian Pharmaceutical Benefits Scheme (PBS). Methods: A cross‐sectional study was conducted using data from MedicineInsight, an Australian database of general practice electronic health records, from March 2016 to August 2018. We compared sociodemographic, comorbidity, and clinical characteristics of patients aged at least 18 years who were prescribed at least one DAA in the first 4 months of PBS listing in 2016 with those prescribed at least one DAA in 2018. Results: There were 2251 eligible adult patients prescribed a DAA during the study period, 62% were men and 59% were aged 50 years and older. Patients prescribed DAA medicines initially were older (aged ≥50 years: 67.9% vs 49.3%; P  < 0.001), and more likely to have liver cirrhosis (14.2% vs 8.4%; P  = 0.01) and an aminotransferase to platelet ratio index (APRI) score >1 (20.4% vs 8.9%; P  < 0.001) than those prescribed DAA medicines in 2018. A greater proportion of patients in regional/remote (46.5% vs 35.6%; P  < 0.001) and socioeconomically disadvantaged areas (44.4% vs 34.5%; P  = 0.003) accessed treatment in 2018 compared with 2016. Conclusions: Despite evidence of decreasing uptake of DAA medicines across Australia, this study indicates broadened uptake among younger age groups and those residing in regional/remote and socioeconomically disadvantaged areas since 2016. While uptake of DAA medicines in some population subgroups appears to have improved, continuous efforts to improve uptake across the Australian population are essential. Abstract : Despite evidence of decreasing uptake of direct acting antiviral (DAA) medicines across Australia, there has been broadened uptake among younger age groups and those residing in regional/remote and socioeconomically disadvantaged areas since 2016. Although uptake of DAA medicines in some population subgroups appears to have improved, continuous efforts to improve uptake across the Australian population are essential.